Investigating the effect of mouth guard use on aerobic performance in amateur boxers. Issue 5 (29th March 2021) - Ahmed, Irfan; Kipps, Courtney; Fine, Peter
Abstract: Objectives: To assess if wearing a mouth guard impacts maximal aerobic capacity in amateur boxers. Materials and Methods: A prospective crossover cohort (pilot) study was conducted to assess maximal aerobic capacity in amateur boxers using the 20 m multi stage fitness test (MSFT). Two primary outcomes measures were recorded: (1) the maximum oxygen uptake (peak VO2 —mL/kg/min) and (2) distance run (meters—m). Thirteen amateur boxers completed the MSFT 7 days apart under control (no mouth guard—C) and intervention conditions (mouth guard—MG). Participants also submitted data on height, weight, type of mouth guard and Rate of Perceived Exertion (RPE) during the test. Statistics: Paired T ‐test. Results: Mouth guard use was shown to reduce peak VO2 and distance run during the 20 m MSFT from 56.31 to 54.12 mL/kg/min and 2572 to 2380 m respectively ( p < 0.05). Twelve out of 13 participants wore a Boil & Bite mouthguard and recorded lower peak VO2 scores (−4.38%) when wearing a mouth guard compared to control conditions, (Mean = −2.46 mL/kg/min, Range of decrease = 4.2–0.9 mL/kg/min; p < 0.05). Ten participants submitted data on RPE—One participant with a custom made mouthguard reported no change in RPE in mouthguard conditions, while nine participants reported an average (+30.5%) increase in mean RPE in Boil & Bite mouthguard conditions compared to control conditions. Conclusions: Boil & Bite mouth guard use was shown to significantly reduce aerobic performance in amateur boxers and increase the perceived rate of exertion during the 20 m MSFT.